2022
DOI: 10.3389/fphar.2022.850066
|View full text |Cite
|
Sign up to set email alerts
|

TLRs-JNK/ NF-κB Pathway Underlies the Protective Effect of the Sulfide Salt Against Liver Toxicity

Abstract: Hydrogen sulfide (H2S) is an endogenously gas transmitter signaling molecule with known antioxidant, anti-inflammatory, and cytoprotective properties. Although accumulating evidence shows the therapeutic potential of H2S in various hepatic diseases, its role in cyclophosphamide (CP)-induced hepatotoxicity remains elusive. The present study was undertaken to investigate the impact of endogenous and exogenous H2S on toll-like receptors (TLRs)-mediated inflammatory response and apoptosis in CP-induced hepatotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In a previous study, NaHS was also shown to cause a reduction in TRL2/4, NF-kB, and TNF-α levels. 37 In another study, CP led to a significant elevation in the levels of proinflammatory cytokines including TNF-α and IL-6 which are involved in the mechanism of tissue damage. 44 In the study, NaHS was also able to reduce IL-6 levels which were elevated by CP administration.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In a previous study, NaHS was also shown to cause a reduction in TRL2/4, NF-kB, and TNF-α levels. 37 In another study, CP led to a significant elevation in the levels of proinflammatory cytokines including TNF-α and IL-6 which are involved in the mechanism of tissue damage. 44 In the study, NaHS was also able to reduce IL-6 levels which were elevated by CP administration.…”
Section: Discussionmentioning
confidence: 97%
“…This was explained by the inhibition of transduction via NF-kB. 35 In addition, H 2 S can regulate angiogenesis through selective potentiation of other molecules such as NO and CO. 36 Recently, Raina et al 37 investigated the effects of endogeneous and exogeneous H 2 S on toll-like receptors (TLRs) – mediated inflammatory response and apoptosis in the CP-induced hepatotoxicity model. In this study, NaHS, an H 2 S donor agent, at a dose of 100 µmol/kg, and dl-propargylglycine (PAG), an H 2 S blocker, at a dose of 30 mg/kg were administered to rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cy is inactive in vitro and functions in vivo primarily through the hydrolysis by hepatic P450 enzymes into aldehyde phosphamide [ 2 ], which interferes with DNA and RNA function. Cy could affect the cell cycle, thereby inhibiting the proliferation of T and B lymphocytes [ 3 ], resulting in immune suppression [ 4 , 5 ]. At present, many natural bioactive substances are currently explored to treat immune function decline [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%